How Gratitude Influences Customer Word-Of-Mouth Intentions and Involvement: The Mediating Role of Affective Commitment. Issue 2 (3rd April 2017) - Fazal-e-Hasan, Syed Muhammad; Lings, Ian N.; Mortimer, Gary; Neale, Larry
Abstract : This current research examines how gratitude and affective commitment work together to improve customer–organizational relationships. Using theories from services marketing and consumer psychology, we develop and test a customer relationship model. The results empirically demonstrate that affective commitment mediates the relationship between gratitude and customer word-of-mouth intentions and involvement. For theorists, our customer relationship model offers a better psychological explanation of how a customers' emotional response of gratitude generates benefits for organizations. We suggest managers should invest in stimulating both customer gratitude and affective commitment to improve positive word-of-mouth intentions and customer involvement subsequently.